2018
DOI: 10.1126/scitranslmed.aap9840
|View full text |Cite|
|
Sign up to set email alerts
|

Squalene epoxidase drives NAFLD-induced hepatocellular carcinoma and is a pharmaceutical target

Abstract: Nonalcoholic fatty liver disease (NAFLD)-induced hepatocellular carcinoma (HCC) is an emerging malignancy in the developed world; however, mechanisms that contribute to its formation are largely unknown, and targeted therapy is currently not available. Our RNA sequencing analysis of NAFLD-HCC samples revealed squalene epoxidase () as the top outlier metabolic gene overexpressed in NAFLD-HCC patients. Hepatocyte-specific transgenic expression in mice accelerated the development of high-fat, high-cholesterol die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
197
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(228 citation statements)
references
References 40 publications
5
197
1
2
Order By: Relevance
“…Upregulation of the metabolic genes ( ALDH18A1 , CAD , CHKA , POLD4 , PSPH , SQLE ) may function in accelerating cellular metabolism. Of note, SQLE (squalene epoxidase) encodes a rate-limiting enzyme in cholesterol biosynthesis and exerts oncogenic roles in cancers 32 34 . Our team has recently revealed that upregulation of SQLE plays an important oncogenic role in driving NAFLD-HCC 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of the metabolic genes ( ALDH18A1 , CAD , CHKA , POLD4 , PSPH , SQLE ) may function in accelerating cellular metabolism. Of note, SQLE (squalene epoxidase) encodes a rate-limiting enzyme in cholesterol biosynthesis and exerts oncogenic roles in cancers 32 34 . Our team has recently revealed that upregulation of SQLE plays an important oncogenic role in driving NAFLD-HCC 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, SQLE (squalene epoxidase) encodes a rate-limiting enzyme in cholesterol biosynthesis and exerts oncogenic roles in cancers 32 34 . Our team has recently revealed that upregulation of SQLE plays an important oncogenic role in driving NAFLD-HCC 32 . CFD encodes human adipsin that functions as an adipokine and regulates insulin secretion 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, in hepatocellular carcinoma induced by non-alcoholic fatty liver disease, SQLE expression is dramatically elevated. Enhanced levels of SQLE cause downregulation of PTEN expression and subsequent activation of Akt signalling, thus increasing CE levels and facilitating cancer development 64 . In summary, whereas oncogenes promote active cholesterol biosynthesis and facilitate tumour growth, tumour suppressors antagonize this overactivated state and maintain cholesterol homeostasis (Fig.…”
Section: Enriched Cholesterol Derivatives: Cholesteryl Esters and Oxymentioning
confidence: 99%
“…In human NAFLD-induced HCC and HCC, SQLE was overexpressed and its expression was associated with poor patient outcomes. Terbinafine, an SQLE-targeting drug, markedly inhibited SQLE-induced cell growth in NAFLD-induced HCC and HCC cells and attenuated tumor development in xenograft models and SQLE transgenic mice 66,67 . These findings are consistent with observations from Stopsack et al and Brown and his colleagues.…”
Section: Sqlementioning
confidence: 99%